P500 Real life 2 year experience with ustekinumab in a Spanish open-label cohort of ulcerative colitis patients. (30th January 2023) - Iborra Colomino, M I; Ferreiro-Iglesias, R; Martín-Arranz, M D; Mesonero-Gismero, F; Mínguez, A; Porto Silva, S; García-Ramírez, L; García de la Filia, I; Bastida, G; Nieto García, L; Suárez Ferrer, C; Aguas, M; et al.
Abstract: Background: Ustekinumab has been recently approved for the treatment of moderately to severe ulcerative colitis (UC). Data from the UNIFI clinical trial are encouraging; nevertheless, real-world assessment is needed. We assess the effectiveness, safety and pharmacokinetics of ustekinumab in a cohort of refractory UC patients. Methods: Multicentre and observational study of UC patients who received ustekinumab for active disease. Values for Partial Mayo Score (PMS), endoscopic activity, C reactive protein (CRP) and faecal calprotectin (FC) were recorded at baseline and at weeks 8, 24 and 52 weeks and at 18 and 24 months when was possible. Demographic and clinical data, previous treatments, adverse events (AEs), surgeries and hospitalizations were documented. Possible predictors of response were examined. Results: One hundred and eight patients were analyzed (Table 1). Two patients only received the first IV dose. During follow-up, 58 patients (54%) required interval reduction (every 4 weeks (76%) and every 6 weeks (24%)) after a median of 22.3 weeks [11.6, 41.2]. Intravenous reinduction doses were administered to 20 (18.5%) after 27.7 weeks [6.64, 56.3]. Three patients required a maintenance therapy with IV administration. The clinical remission (PMS≤ 2) rates were 39.6%, 41%, 51% at 8, 24 and 52 weeks, respectively, and 61%, and 57.7% at 18 and 24 months, respectively. FC levels returned to normal (<250 μg/g) in the 39.6%, 41%, 51%, 61%, 58% of the patients at weeks 8, 24 and 52 and at 18 and 24 months respectively. CRP returned to normal (<3 mg/L) in the 79%, 75%, 76.5%, 71% and 70% of the patients at weeks 8, 24 and 52 and at 18 and 24 months respectively. PMS, FC and CRP values and ustekinumab through levels over time are shown in Figure. Fewer previous anti‐TNF agents and the loss of response to anti-TNF were associated with clinical response and with normalization of FC respectively. No variables at baseline (body mass index, serum albumin, and lymphocytes count) were associated with ustekinumab through levels. Of the 17 patients with endoscopy before and after treatment, 6 were in remission and 3 with mild activity. The AEs were recorded in 5 (4.6%) patients, 12 (11%) were hospitalized and 9 (8.3%) had surgery. A total of 23 patients (21%) discontinued ustekinumab over time, the persistence rates were 98%, 91%, 83% and 81% at 8, 24, 48 and 96 weeks respectively. Conclusion: This is the first study to show the real‐world long-term effectiveness, persistence, endoscopic improvement and safety of ustekinumab in a cohort of highly refractory UC patients. The clinical remission preceded the FC normalization. Ustekinumab through levels and their pharmacokinetic require further investigations.